2023
DOI: 10.1186/s12871-023-02042-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of cardiovascular interventions to decrease blood loss during hepatectomy: a systematic review and meta-analysis

Abstract: Background Perioperative bleeding and allogeneic blood transfusion are generally thought to affect the outcomes of patients. This meta-analysis aimed to determine the benefits and risks of several cardiovascular interventions in patients undergoing hepatectomy. Methods In this systematic review and meta-analysis, randomised controlled trials (RCTs) were searched in the Cochrane Library, Medline, Embase, and Web of Science to February 02, 2023. RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…14,15 ANH, either alone or in conjunction with a low CVP strategy, significantly decreased the need for allogeneic blood transfusions during hepatectomy. 16,17 We specifically found that when TXA was combined with ANH, the median blood loss was 700 mL (13.3 mL/kg), a substantial reduction compared to the 1200 mL (20.4 mL/kg) observed in the ANH-only group, with statistical significance (P < 0.05). While two out of the 15 patients in the TXA and ANH group required blood transfusions and plasma infusions during the operation, this figure was lower than the 4 patients in the ANH-only group, although this difference did not reach statistical significance (P > 0.05), likely due to the small sample size.…”
Section: Discussionmentioning
confidence: 85%
“…14,15 ANH, either alone or in conjunction with a low CVP strategy, significantly decreased the need for allogeneic blood transfusions during hepatectomy. 16,17 We specifically found that when TXA was combined with ANH, the median blood loss was 700 mL (13.3 mL/kg), a substantial reduction compared to the 1200 mL (20.4 mL/kg) observed in the ANH-only group, with statistical significance (P < 0.05). While two out of the 15 patients in the TXA and ANH group required blood transfusions and plasma infusions during the operation, this figure was lower than the 4 patients in the ANH-only group, although this difference did not reach statistical significance (P > 0.05), likely due to the small sample size.…”
Section: Discussionmentioning
confidence: 85%
“…The central venous catheter (CVC) is a standard of care for liver transplantation [1 && ,29,105]. A recent review of literature showed that low central venous pressure (LCVP) decreases surgical bleeding and improves postoperative outcomes in hepatectomies including in pediatrics [10,56]. The threshold for LCVP is traditionally less than 5 mmHg; however, a recent study showed that a LCVP of less than 8 mmHg is equally beneficial and more practical to reach and correlates with a stroke volume variation (SVV) more than 13% [55].…”
Section: Central Venous Cathetermentioning
confidence: 99%